Evaluating the Efficiency of Turkish Banks: A Risk and Profitability Approach - Eken, Mehmet Hasan (2013)
Conventional performance indicators, especially after recent financial restructuring initiatives, are criticized more than ever for not associating performance and risk. The purpose of this study is to benchmark performance of banks in comparison to risk-taking preferences, under different models with data envelopment analysis, to evaluate whether risks are reasonably priced. Comparing a bank’s risk efficiency with its competitors may provide additional insights to regulatory and supervisory authorities together with bank management. The results indicate that profitability of banks is not necessarily parallel with their risk-taking preferences. Banks with low risk efficiency should revise their business style for potential improvements.